(untitled) (Marketing Journal, 2025)
The article "Factors of Income Diversification in the Context of an Innovative Economy " analyzes the main factors influencing the diversification of population and regional incomes amid technological development and innovation -driven growth. The authors examine structural changes in the labor market, the impact of digitalization, and the emergence of new economic sectors, highlighting their role in shaping diverse sources of income. The study places particular emphasis on the importance of human capital, entrepreneurial activity, and institutional support mechanisms as key enablers of income base expansion. The article offers both theoretical and practical recommendations aimed at enhancing income stability and reducing inequality in an innovation -oriented economy.